Species-specific effects of climate change on the distribution of suitable baboon habitats – Ecological niche modeling of current and Last Glacial Maximum conditions. Issue 132 (July 2019) - Chala, Desalegn; Roos, Christian; Svenning, Jens-Christian; Zinner, Dietmar
Abstract: Baboons (genus Papio ) have been proposed as a possible analogous phylogeographic model for intra-African dispersal of hominins during the Pleistocene. Previous studies of the genus reveal complex evolutionary dynamics including introgressive hybridization and, as for hominins, it has been hypothesized that past climate change has been a major driver in their evolutionary history. However, how historical climate changes affected the distribution and extent of baboon habitats is not clear. We therefore employed three ecological niche modeling algorithms (maximum entropy model: MaxEnt; general additive model: GAM; gradient boosting model: GBM) to map suitable habitat of baboons at both genus and species levels under two extreme late-Quaternary climates: current (warm period) and Last Glacial Maximum (LGM, cold period). The three model algorithms predicted habitat suitabilities for the baboon species with high accuracy, as indicated by AUC values of 0.83–0.85 at genus level and ≥0.90 for species. The results suggest that climate change from LGM to current affected the distribution and extent of suitable habitats for the genus Papio only slightly (>80% of the habitat remained suitable). However, and in contrast to our expectation for ecological generalists, individual species have been differentially affected. While P. ursinus and P. anubis lost some of their suitable habitats (net loss 25.5% and 13.3% respectively), P. kindae and P. papio gained large portions (net gain >62%), and P. cynocephalus and P. hamadryas smaller portions (net gain >20%). Overlap among the specific realized climate niches remained small, suggesting only slight overlap of suitable habitat among species. Results of our study further suggest that shifts of suitable habitats could have led to isolation and reconnection of populations which most likely affected gene flow among them. The impact of historic climate changes on baboon habitats might have been similar for other savanna living species, such as hominins.